Assessing the changes in drought conditions during summer in the Republic of Moldova based on RegCM simulations - Potop, Vera; Boroneant, Constanta; Caian, Mihaela (Journal of Economic Development, Environment and People, 2013)
We assess the changes in drought conditions during summer in the Republic of Moldova based on the Standardized Precipitation Index (SPI) calculated from monthly precipitation data simulated by the regional climatic model RegCM3. The RegCM simulations were conducted at a horizontal resolution of 10 km in the framework of EU-FP6 project -CECILIA. The domain was centered over Romania at 46°N, 25°E and included the Republic of Moldova.